Chinese Credit Card Interest Rate: Recent Credit Card Pricing Model Progress and the Comparative Study - Wang, Ting (2008)
In recent years, while the cost of funds has fallen, credit card rates have remained stubbornly high, spurring legislators to consider imposing interest rate ceilings on credit card rates.